Haptic Dissection of Deformable Objects using Extended Finite Element Method - Li, Ziyun (Université d'Ottawa / University of Ottawa, 2014)
Interactive dissection simulation is an important research topic in the virtual reality (VR) community. There are many efforts on this topic; however, most of them focus on building a realistic simulation system regardless of the cost, and they often require expensive workstations and specialized haptic devices which prevent broader adoption. We show how to build a realistic dissection simulation at an affordable cost, which opens up applications in elementary education for virtual dissections which are currently not feasible. In this thesis, we present a fast and robust haptic system for interactive dissection simulations of finite elements based deformable objects which supports two type of haptic interactions: point contacts and cuts. We design a semi-progressive virtual dissection scheme of deformable objects in a real-time application. The quality and performance of visual/haptic feedback is demonstrated on a low-end commercial desktop PC with a haptic device.
Keywords: Haptic; Dissection; Solid Deformation; FEM; XFEM